1996
DOI: 10.1046/j.1365-2141.1996.5191061.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Features and Prognosis in 72 Patients With Multiple Myeloma Who Were Younger Than 40 Years

Abstract: The purpose of this study was to analyse the presenting clinical and laboratory features and the outcome of 72 patients with multiple myeloma (MM) who were younger than 40 years. The records of all Mayo Clinic patients with MM younger than 40 years who were seen between 1 January 1956 and 31 December 1992 were reviewed. Survival was measured from the date when treatment was required to the date of last follow-up or death. The frequency of MM in patients younger than 40 and 30 years in 3278 Mayo Clinic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
128
3
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 23 publications
8
128
3
8
Order By: Relevance
“…However we could not get any cases below the age of 30 years. Our finding is similar to the study done by Blade et al (1996).Though the obvious jaundice was not reported in our study, serum level of bilirubin (all total, direct and indirect) was found to be significantly higher compared with control groups. Observation of symptomatic liver disease is very rare in multiple myeloma and occasional jaundice may be seen (Thomas et al, 1985) which is almost associated with the amyloid deposition in hepatic tissues (Yamamoto et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…However we could not get any cases below the age of 30 years. Our finding is similar to the study done by Blade et al (1996).Though the obvious jaundice was not reported in our study, serum level of bilirubin (all total, direct and indirect) was found to be significantly higher compared with control groups. Observation of symptomatic liver disease is very rare in multiple myeloma and occasional jaundice may be seen (Thomas et al, 1985) which is almost associated with the amyloid deposition in hepatic tissues (Yamamoto et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…33 However, this same group is known to have an improved survival with standard melphalan chemotherapy. 34 One cannot overemphasize the importance of tumor biology in predicting the outcome of myeloma transplant studies. Virtually all published studies indicate that high ␤ 2 -microglobulin concentration, high labeling index, and low hemoglobin levels are adverse prognostic factors in highdose therapy and stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the median age of HIV-negative patients with MGUS is 64 years, with only 4% younger than 40 years, and a 10 year period before the development of plasma cell neoplasm in the subpopulation that progresses; 12 Ishida and Dorfman 77 found fewer than 25 well-documented reports in the literature of multiple myeloma occurring before the age of 30 years. Two recent reports from Kyle's group have described patients with myeloma under the age of 40 (only 2% of myeloma patients) 78 and under the age of 30 (only 0.3% of myeloma patients). 79 In contrast to the general population, the mean patient age in the reported cases of MGUS, plasmacytoma and myeloma in AIDS patients is 33 years (34 years for MGUS, 32 years for documented neoplasms).…”
Section: Gammopathy and Plasma Cell Tumors In Aidsmentioning
confidence: 99%